Prevalence and determinants of smoking in some selected private university students of Dhaka city - Huq, SA; Hossain, SM; Zahid, Mizan; Haque, SMT; Chowdhury, TG (Update Dental College Journal, 2016)
This descriptive type of cross-sectional study was conducted to assess the prevalence and determinants of smoking among some selected private university students of Dhaka city in Bangladesh with sample size of 190. The students were aged between 18 and 26 years with mean age as 22.42 ± 1.820. The majority of the respondents (82.1%) were of the nuclear family and 63.2% were living with their friends. Among the smokers (n=187) 50.5% spent Tk. 91-130 and 26.3% spent Tk. 131-170 for smoking daily. The present study also revealed that 98.4% students were smokers of whom 79.7% started smoking at ages between 13 to15 years. Among them 42.5% smoked 12-16 cigarettes, 27.4% smoked 17-21 cigarettes per day and rest 19.4%, 7.0% and 3.8% were taking 22-26 , 2-6 and 7-11 cigarettes per day. Regarding knowledge on hazards associated with smoking 39% mentioned it was loss of money and 35.2% mentioned lung cancer. The study further revealed that 93% smoked due to peer pressure and 91.4% got intervention to quit smoking. Of them 39.8% received counseling from friends as intervention. A significant association was found from this study between number of cigarette taken per day with living partner (p= 0.000). As smoking kills the smokers, awareness program to be lunched in a way so that people voluntary leaves the habit. Update Dent. Coll. j: 2015; 5 (2): 40-46